PLAYING VIDEO GAMES IN READING AND ITS EFFECTIVENESS FOR ENGLISH LEARNERS - Arya Bangun Pamungkas (JOLE (Journal of Language Education), 2023)
Video games are not always harmful; in fact, they can have positive effectson English language learning. Games that use English as a means ofcommunication can indirectly help non-native English speakers improvetheir reading skills. As gaming has become an integral part of daily life,especially for students who often use gadgets like computers, tablets, orsmartphones, it presents an opportunity for enjoyable and effectivelearning. The purpose of this study is to examine why participants playvideo games and how it can aid in their English language learning. Thestudy gathered data through in-depth interviews with ten individuals fromdifferent backgrounds who shared a passion for video games andrecognized their potential for improving English reading skills. Theparticipants cited entertainment, story-driven games, competition, socialinteraction, and stress relief as reasons for playing video games. All agreedthat video games had helped them significantly in improving their Englishreading skills.